2019
DOI: 10.5339/qmj.2019.4
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination coverage in Qatar: Benchmarking with global figures

Abstract: Introduction: Vaccination is considered one of the most successful and cost-effective public health interventions of the 20 th century. In 2017, Qatar's Expanded Program of Immunization (EPI) provided vaccination services against a comprehensive list of 15 vaccine-preventable diseases. Objectives: To assess the performance of Qatar's national immunization system, identify possible gaps by determining the national vaccination coverage rates, and benchmark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…A similar matched case-control study conducted in Qingdao, China, showed a 44.7% vaccine effectiveness for one-dose and an 81.6% for two-dose vaccinations. It is possible that the low one-dose vaccine effectiveness compared to ours is due to the age group included in this study (6)(7)(8)(9)(10)(11) which is reflective of the fact that one dose of the varicella vaccine does not induce an adequate immune response for lifelong immunity. By the age of 5, immunity wanes and hence a second dose is required to boost the immune system [33].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A similar matched case-control study conducted in Qingdao, China, showed a 44.7% vaccine effectiveness for one-dose and an 81.6% for two-dose vaccinations. It is possible that the low one-dose vaccine effectiveness compared to ours is due to the age group included in this study (6)(7)(8)(9)(10)(11) which is reflective of the fact that one dose of the varicella vaccine does not induce an adequate immune response for lifelong immunity. By the age of 5, immunity wanes and hence a second dose is required to boost the immune system [33].…”
Section: Discussionmentioning
confidence: 86%
“…In Qatar, varicella infection is the second most common notifiable disease, although the vaccine coverage rate is currently estimated at 95%, one of the highest rates in the world [11,12]. According to Qatar's pediatric vaccination schedule (Supplementary Figure S1), two doses of varicella vaccine are provided for free, the first dose is given at 1 year of age and the second dose is given between 4 and 6 years of age [13].…”
Section: Introductionmentioning
confidence: 99%
“…With relatively high per capita health expenditure among the Gulf Cooperative Council (GCC) states, good quality healthcare is provided to all Qatari nationals and residents at greatly subsidized rates [ 19 ]. An existing national immunization program provides protection against 15 vaccine-preventable diseases in line with locally and globally identified disease trends [ 21 ].…”
Section: Introductionmentioning
confidence: 99%